Efficacy of Memantine, Donepezil, or Their Association in Moderate-Severe Alzheimer’s Disease: A Review of Clinical Trials - Ivana Molino; Luisa Colucci; Angiola M. Fasanaro; Enea Traini; Francesco Amenta (The Scientific World Journal)
Background. Acetylcholinesterase (AChE)/cholinesterase (ChE) inhibitors (Is) and memantine are licensed for symptomatic treatment of mild-moderate and moderate-severe forms of Alzheimer’s disease (AD), respectively. High doses of the AChE-I donepezil were licensed in the USA for moderate-severe AD, and the association AChE/ChE-Is plus memantine was proposed for AD at this stage. Objectives. This paper has reviewed evidence from clinical trials of the effectiveness of memantine, donepezil, or the two drugs in association in managing moderate-severe AD. Method. Double-blind, placebo-controlled randomized trials (RCTs) using memantine or donepezil alone or in association versus placebo in moderate-severe AD were reviewed. Analysis done in January 2013 considered the years 2007–2012. Results and Conclusion. Only 83 of the 941 papers selected were considered relevant, and only 13 met the criterion of “adequacy and representativeness.” Memantine and donepezil lead to improvements in moderate-to-severe AD and the choice between the compounds should be based on their contraindications more than on disease severity. No evidence was found of advantages of the association of memantine-donepezil. The heterogeneity of conditions explored by RCTs, the relatively short time of observation (24–52 weeks), and the different cognitive assessment tools used did not allow comparing properly different trials.